Efektivitas Model Peningkatan Kompetensi Profesional Guru Biologi Berbasis Continuous Professional Development (CPD) di Karesidenan Surakarta - Anif, Sofyan; Zain, Almuntaqo (Universitas Muhammadiyah Surakarta, 2015)
The Indonesian Law No. 14 Year 2005 on teacher and lecturer and Government Regulation No 74 Year 2008 on teacher, have mandated the government to carry out certi? cation for teachers of all subjects who have met the requirements. Based on a survey conducted by the Directorate General of Quality Improvement of Teachers and Education Personnel (PMPTK) in 2009, the certi? cation program has not been able to improve the competence and professionalism of teachers signi? cantly so it has not given positive in? uence on improving the performance of teachers. The purpose of this study is to determine the effectiveness of the model of professional competence improvement of biology teacher based on initial competence test in Surakarta.This research uses R & D approach developed by Borg and Gall (2007), which includes six procedures or stages of development: (1) determine the product; (2) conduct a theoretical and empirical study; (3) development planning; (4) the development of early models; (5) validation of the model; and (6) the discovery of the ? nal product. The ? rst up to the fourth stage has been done in previous studies, and this research is the ? fth stage namely the stage of model validation through limited experiment with one-group pretest-Posttest Design. While the data analysis uses traditional descriptive quantitative approach.The results of the study on the effectiveness of implementation of the model of increasing Biology teacher competence based on CPD on a limited scale test show that the classical absorption of pretest is 27.78%, while the classical absorption of post-test is 72.22%. It means that Biology teacher competence based on CPD has increased in a limited test scale of 44.44%. The results of a statistical analysis of the increase of pre- test and post-test absorption on each competence shows that the greatest increase of percentage in absorption was on the competence: ?understanding the concepts, laws, and theories of biology and ? exible implementation? for 38.89%. While the lowest increase of percentage in the absorption occurred on the competence: ?conducting action research to increase professionalism? with only 13.27%.